Scholars Raising their Voices Up: An Approximation to Discourses of Hegemony and Resistance in ELT in Colombia - Jhon Eduardo Mosquera Pérez (Ikala: Revista de Lenguaje y Cultura, 2022)
In the last few years, Colombian ELT scholars have become aware of the importance of discourse for the dissemination of ideologies and agendas. As a result, the number of studies on this area has shown an unprecedented growth. Nevertheless, few investigations have explored and analyzed both sides simultaneously so as to display not only the types of hegemonic discourses that have permeated the field but also those which have recently emerged in response to such a situation. Considering these elements, this paper reports on a qualitative case study carried out with the purpose of analyzing the latest types of hegemonic discourses and discourses of resistance that have taken place in elt in Colombia. After analyzing the data gathered, which consisted of empirical and conceptual articles, as well as linguistic policies emitted by the Colombian Ministry of Education (men), the results showed that discourses revolving around bilingualism (understood as the English-Spanish relationship), identity, and native speakerism have been a recurrent aspect in the Colombian elt field. Yet, findings also suggest that, especially in the last decade, elt scholars have been resisting these discourses by promoting alternative ones that acknowledge initiatives in different areas of knowledge. In light of these aspects, it is recommended to keep resisting and promoting an agenda of decolonization so that alternative discourses, as is the case of those that acknowledge the incorporation of epistemologies that have been historically overlooked, continue gaining traction within the field.